PENERAPAN METODE INKUIRI TERBIMBING UNTUK MENINGKATAN PEMAHAMAN SISWA TUNARUNGU MATERI PENJUMLAHAN PECAHAN DI SLBN TALUN BLITAR - SRI HARTATI (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2022)
This study aims to (1) obtain an overview of the implementation of mathematics learning in the material of adding fractions at SLB Negeri Talun by using the inquiry method and (2) describing the implementation of the results of increasing understanding of the material for adding fractions using the guided inquiry method at SLB Negeri Talun. This research was conducted in the odd semester of the 2021/2022 academic year. This study focuses on the mathematics subject matter of adding fractions in class V by applying the guided inquiry method. The time of this research was carried out in two cycles, the first cycle on 20 to 21 September 2021 while the second cycle on 27 to 28 September 202I. The object of this research are three students of class V Deaf SLB Negeri Talun, Blitar district. This study uses a classroom action research (CAR) design. The conclusions of this study are as follows: (1) The application of the guided inquiry method in improving students' understanding, especially in understanding the material for adding fractions has a positive influence, namely it can increase students' interest in learning which is indicated by an increase in the percentage of student interest in learning from the first cycle of 33.00% to 100% on slikus. This means, students' interest in learning belongs to the very active category because the increase in student interest in learning is 67.00% and (2) The application of learning outcomes of fraction addition material with understanding using the guided inquiry method has increased very well. It can be seen that in the first cycle, of the 3 students who completed as many as 1 student (33%) and who had not completed only 2 students (66%) while in the second cycle, all students who completed were all students (100%) and none unfinished (0%). From cycle I to cycle II there was an increase in learning outcomes by 66%. ABSTRAKPenelitian ini bertujuan untuk (1) Memperoleh gambaran pelaksanaan pembelajaran matematika materi penjumlahan pecahan di SLB Negeri Talun dengan menggunakan metode inkuiri dan (2) Mendiskripsikan penerapan hasil peningkatan pemahaman terhadap materi penjumlahan pecahan dengan menggunakan metode inkuiri terbimbing di SLB Negeri Talun. Penelitian ini dilakukan pada semester ganjil tahun pelajaran 2021/2022. Penelitian ini menitikberatkan pada mata pelajaran matematika materi penjumlahan pecahan kelas V dengan menarapkan metode inkuiri terbimbing. Waktu penelitian ini dilaksanakan dalam dua siklus, siklus I pada tanggal 20 s.d 21 September 2021 sedangkan siklus II pada tanggal 27 s.d 28 September 202I. Objek penelitian ini adalah tiga siswa kelas V Tunarungu SLB Negeri Talun, kabupaten Blitar. Penelitian ini menggunakan desain penelitian tindakan kelas (PTK). Kesimpulan dari penelitian ini ialah sebagai berikut: (1) Penerapan metode inkuiri terbimbing dalam meningkatkan pemahaman siswa terutama dalam memahami materi penjumlahan pecahan mempunyai pengaruh positif, yaitu dapat meningkatkan minat belajar siswa yang ditunjukan dengan peningkatan prosentase minat belajar siswa dari siklus I sebesar 33.00% menjadi 100% pada slikus. Hal ini berarti, minat belajar siswa tergolong dalam kategori sangat aktif karena peningkatan minat belajar siswa sebesar 67.00 % dan (2) Penerapan hasil belajar materi penjumlahan pecahan dengan pemahaman mengunakan metode inkuiri terbimbing terbimbing mengalami kenaikan yang sangat baik. Hal ini dapat dilihat bahwa pada siklus I, dari 3 siswa yang tuntas sebanyak 1 siswa (33%) dan yang belum tuntas hanya sebanyak 2 siswa (66%) sedangkan pada siklus II, siswa yang tuntas semua siswa (100%) dan tidak ada yang belum tuntas (0%). Dari siklus I ke siklus II ada peningkatan hasil belajar sebesar 66 %.